Semidetached SUP-Subalgebras of Sheffer Stroke UP-Algebras (European Journal of Pure and Applied Mathematics, 2025)
The notion of semidetached Sheffer stroke UP-algebras is introduced, and their properties are investigated. Several conditions for a semidetached structure in Sheffer stroke UP-algebras to be a semidetached SUP-subalgebra are provided. The concepts of $(\overline{\in},\overline{\in}\vee \overline{q_k})$-fuzzy SUP-subalgebra, $k$-left ($k$-right) $(q_k, \overline{\in}\vee \overline{q_k})$-fuzzy SUP-subalgebra, $(q_k, \overline{\in}\vee \overline{q_k})$-fuzzy SUP-subalgebra and $(\overline{\in}\vee \overline{q_k}, \overline{\in}\vee \overline{q_k})$-fuzzy SUP-subalgebra are introduced, and relative relations and properties are discussed.
Keywords: Sheffer stroke UP-algebra; $(\in,\overline{\in}\vee \overline{q_k})$-fuzzy SUP-subalgebra; $k$-left ($k$-right) $(q_k, \overline{\in}\vee \overline{q_k})$-fuzzy SUP-subalgebra; $(\overline{\in}\vee \overline{q_k}; \overline{\in}\vee \overline{q_k})$-fuzzy SUP-subalgebra; semidetached SUP-subalgebra